Fighting falsified medicines with paperwork – a historic review of Danish legislation governing distribution of medicines. Issue 1 (December 2016) - Borup, Rasmus; Kaae, Susanne; Minssen, Timo; Traulsen, Janine
Abstract Background Many areas of pharmaceutical legislation in the European Union (EU) are harmonised in order to promote the internal market and protect public health. Ideally, harmonisation leads to less fragmented regulation and cross-border complexities. This study, however, focuses on an increasingly harmonised legislative area that is subject to increases in requirements and complexities: the distribution of medicines. This study compared Danish legislation governing the distribution of medicines before and after Denmark joined the EU in order to assess the impact of EU harmonisation, as well as to evaluate whether the drastic increases in requirements mandated by the Falsified Medicines Directive of 2011 correspond to a new approach to governing the pharmaceutical supply chain. Methods A review was conducted of 115 applicable Danish laws, executive orders and guidelines from 1913 to 2014. Legal requirements were organised according to the year they were published and the companies they affected. Greater changes in legislative requirements were developed through inductive content analysis. Results Early legislation positioned pharmacies as gatekeepers, requiring them to identify and stop medicines of substandard quality. Legislation to regulate the supply chain was slow to materialise. After Denmark joined the EU, the scope of legislation widened to include all actors in the supply chain, and the quantity of legislation increased dramatically. Simultaneously, requirements became more specific, thereby promoting a formalistic interpretation and focusing the attention of companies and authorities on predefined areas with little room to implement innovative solutions. Over time, documentation became the focus of legislation, requiring companies to provide documentary evidence for their compliance with legislation. The Falsified Medicines Directive continues these trends by increasing requirements for documentation and promoting a formalistic interpretation. Conclusion The legislative approach adopted since Denmark joined the EU gives companies and medicine inspectors little room to interpret legislation. The Falsified Medicines Directive does not depart from this approach. Legislation seems more focused on enforcing similar requirements than on benefiting public health. Legislation may benefit from allowing room for local interpretation of requirements.